RESULTADOS OBTIDOS EM 2009-2010 PELO GRUPO DE PESQUISA: PROJETO EM SISTEMAS MECÂNICOS, MECATRÔNICA E ROBÓTICA DA UNIJUÍ - Valdiero, Antonio C.; Bortolaia, Luis A.; Rasia, Luiz A.; Rios, Claudio F.; Ferreira, Franklin d. S.; Hoffmann, Roger S.; Gonçalves, Marcia F.; Pörsch, Marcia R. M. H.; Fracaro, Adonis R.; Hartmann, Ricardo A.; et al. (Salão do Conhecimento, 2013)
Resumo